2020
DOI: 10.1097/md.0000000000020759
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of key gene in sepsis development

Abstract: Sepsis is one of the leading causes of mortality in intensive care units (ICU). The growing incidence rate of sepsis and its high mortality rate result are very important sociosanitary problems. Sepsis is a result of infection which can cause systemic inflammatory and organ failure. But the pathogenesis and the molecular mechanisms of sepsis is still not well understood. The aim of the present study was to identify the candidate key genes in the progression of sepsis. Microarray datasets GSE28750, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…MMP-8 is mainly expressed in neutrophils or macrophages, while at later stages of acute lung injury, it can be released from mesenchymal cells in the airways [ 26 ]. MMP-8 is upregulated in sepsis [ 27 ], although laboratory models and molecular biology only show that its presence ensures neutrophil infiltration in response to lipopolysaccharide [ 28 ], likely through the degradation of LIX CXC chemokines [ 29 ]. This would limit lung inflammation and act as a key mediator in the regulation of innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-8 is mainly expressed in neutrophils or macrophages, while at later stages of acute lung injury, it can be released from mesenchymal cells in the airways [ 26 ]. MMP-8 is upregulated in sepsis [ 27 ], although laboratory models and molecular biology only show that its presence ensures neutrophil infiltration in response to lipopolysaccharide [ 28 ], likely through the degradation of LIX CXC chemokines [ 29 ]. This would limit lung inflammation and act as a key mediator in the regulation of innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the deepening of clinical research on sepsis, more and more new biomarkers provide new ideas for early diagnosis of this comorbidity. 21 Existing studies have found that miRNA has many biological functions in cell animal models, and participates in the occurrence and development of many immune disorders. 22 In an investigation of C57BL/6 mice induced by CLP, the raised miR-539-5p reduced the pulmonary injury and inflammation triggered by CLP.…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al. identified SLC2A3 as a hub gene for sepsis development from three datasets via bioinformatics analysis, and they also revealed that the expression of SLC2A3 was significantly increased in endothelial cells (ECs) upon LPS stimulation ( Fu et al., 2020 ). LPS-induced endothelial inflammation plays a vital role in the progression of sepsis.…”
Section: Discussionmentioning
confidence: 99%